Design and build a positive linear regulator - Tan, Jenny Rui Ping (2018)
This final year project report will explain the background and functions of a linear regulator. Linear regulators are preferred for many applications as they require low cost and are of low complexity. Majority of modern-day electrical appliances, such as computers and printers, require DC power supply. However electrical outlets in Singapore are of approximately 230 V AC, 50 Hz. Thus these appliances require converters to step down the high 230 V AC to a lower voltage. The aim of this project is to develop a positive linear regulator that produces a stable DC supply with negligible ripple voltage. It is mainly a hardware construction project that includes the usage of a 230 V : 6 V transformer. A rectifier circuit will be developed to output DC voltage from AC voltage. Smoothing capacitor is required to even out fluctuations in voltages. Ripple voltage will be measured and compared with theoretical prediction.